The impact of psychological resilience on job performance in a cross-cultural context: evidence from Chinese multinational corporations - WU, Chunlin (Institutional Knowledge at Singapore Management University, 2024)
As globalisation accelerates and multinational companies expand, more employees are being assigned to work in other countries. This phenomenon of international assignments brings business opportunities and numerous challenges, the most prominent being cross-cultural adjustment. Expatriates must face different cultural backgrounds, values, and lifestyles. Such cultural differences can lead to communication barriers, psychological stress, and lifestyle difficulties, subsequently affecting job performance. This study explores the mechanism between psychological resilience and job performance from the perspective of expatriates' cross-cultural adjustment. It conducts empirical research through two rounds of three surveys, collecting 229 valid questionnaires in Cambodia, Thailand, and Vietnam. First, this study introduces psychological resilience within cross-cultural themes, examining its impact on job performance among expatriates. Empirical research using sample data from Cambodia, Thailand, and Vietnam shows a significant direct positive correlation between expatriates' psychological resilience and job performance. This extends the application of psychological resilience theory, and provides an essential basis for selecting expatriate personnel. Second, the study deepens the understanding of how psychological resilience influences job performance. Current there is a lack of empirical research on the mechanism by which the psychological resilience of expatriates impact work performance. This study introduces cross-cultural adjustment as a mediating variable and empirically tests that cross-cultural adjustment is one of the key pathways through which psychological resilience affects job performance. This highlights the need for effective strategies and measures to manage cross-cultural adjustment amid the challenges and pressures of foreign cultures. Third, the study enriches the application of cultural tightness theory. By introducing cultural tightness theory into expatriate research, the study finds that a relatively loose culture aids the cross-cultural adjustment of expatriate staff. Under such conditions, the impact of psychological resilience on cross-cultural adjustment is more pronounced. Fourth, the study incorporates trust in supervisors from a cross-cultural adjustment perspective. The findings suggest that trust in supervisors positively enhances relationship between cross-cultural adjustment and job performance of expatriate employees and will amplify the impact of cross-cultural adjustment on job performance. This conclusion affirms the importance of trusting supervisors from the perspective of international assignees, enriches the research significance of trust in supervisors, and provides practical insights for expatriate personnel management.